The association between vaginal microbiota disorders and early missed abortion: A prospective study - Dan Sun; Xingping Zhao; Qiong Pan; Fang Li; Bingsi Gao; Aiqian Zhang; Huan Huang; Dabao Xu; Chunxia Cheng (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The objective of this study was to explore the association between disordered vaginal microbiota and missed abortion to ascertain potential causes of missed abortion related to vaginal microbiology. Material and methods This study was a prospective cohort study with a comparison group (reference group). Vaginal secretions from the posterior fornix of women in the early stages of pregnancy were collected in the Xiangya Third Hospital of Central South University in Changsha, Hunan, China, from November 2018 to November 2019. A total of 54 cases of missed abortion (case group) and 50 cases of normal pregnancy requiring induced abortion (reference group) were analyzed. Bacterial DNA was extracted, hybridized with gene‐specific primers, and then detected using a bacterial chip. The composition and relative abundance of vaginal microbiota in the two groups were compared using α‐diversity analysis, β‐diversity analysis, and the linear discriminant analysis effect size method. Results The α‐diversity analysis showed that the Simpson index of the case group was lower than that of the reference group, whereas the Shannon index in the case group was higher. The relative abundance of Firmicutes in the case group (42.52%) was lower than in the reference group (51.03%, p < 0.05), as was the relative abundance of Lactobacillus (case group 16.51%, reference group 23.00%; p < 0.05). Interestingly, levels of Mycoplasma genitalium and Ureaplasma were lower in the case group (p < 0.05). The relative abundance of Lactobacillus crispatus, Lactobacillus jensenii, and Lactobacillus gasseri was also significantly lower in the case group than in the reference group (p < 0.05). The pathways enriched in the case group were predominantly related to metabolism, whereas the genetics‐related pathways were predominantly enriched in the reference group. Conclusions Bacteria are more diverse and unevenly distributed in patients with missed abortion. Decreases in the proportion of vaginal Lactobacillus and changes in Lactobacillus species in these patients may increase the chance of genital tract pathogenic bacterial infection. To our knowledge, our study was the first to observe that a decrease of Firmicutes levels in the vaginal microbiota might impair energy metabolism and have an association with missed abortion.